Pangkak Gasing: Tools of Social Interaction of The Community of Children and Adolescents in Maintaining Malay Culture Sambas - Bayu Suratman; Nur Hamzah (Kawalu: Journal of Local Culture, 2022)
This article is based on the results of in-depth research on the pangkak gasing and social interactions of Sambas Malay children and adolescents. Pangkak gasing is a traditional game that is currently running lively in the rural district of Sambas. In addition to preserving the culture of the pangkak gasing, it is also a means of friendship for fellow Malay Sambas. The presence of children and adolescents in apangkak gasing game of forming a habitus in the community arena where social interaction takes place. Social interaction in the arena ( field ) pangkak gasing not only by direct contact during the game but also penetrated in the virtual world or social media. New media in social interaction, especially in the arena ( field) pangkak gasing make social media as a tool to interact where agents have never met and started meeting in the real world. This article discusses how the pangkak gasing affect the social interaction of Sambas Malay children and adolescents. This research uses a qualitative method with a sociology approach. Data was obtained through observations and interviews with Sambas Malay children and adolescents who participated routinely in the pangkak gasing game